OP0014-PARE From Design to Implementation – Patient and Public Involvement in an Nihr Research Programme in Osteoarthritis in Primary Care. (9th June 2015) - Higginbottom, A.; Jinks, C.; Bird, J.; Rhodes, C.; Blackburn, S.; Dziedzic, K.
Abstract : Background: An NIHR funded research programme of linked studies to optimise the management of osteoarthritis (OA) in primary care embedded Patient and Public Involvement (PPI) throughout. Objectives: To describe PPI involvement throughout a large five-year research programme in OA. Methods: PPI followed the INVOLVE framework with projects nested throughout the research cycle. Research User Group (RUG) members helped to shape the development of the research programme, which included a new model of primary care consultations for OA. 1 A PPI co-applicant was named in the programme grant submission. During the research programme, a dedicated OA RUG was formed from existing members of the RUG to contribute to all aspects of the programme. The PPI was funded from the programme grant and supported by a dedicated PPI team. PPI members sat on Steering Committees or advisory groups for individual studies. PPI ranged from designing and managing clinical trials; advising on the interventions; developing information and questionnaires for patients; generating training material for GPs and practice nurses; and reporting findings. Results: PPI views on the development of the OA research programme influenced guidance for patients on self-managing OA and the development of a guidebook about living with OA. The guidebook became a central component of the research programme. PPI members helped interpret patients' views about self-managing OA, which influenced the interventions. Other key achievements included: 1) taking part in a consensus study to devise a model GP consultation for OA (later trialled), 2) developing a questionnaire to assess the quality of primary care consultations for OA, 3) advising on the content and wording of study questionnaires, 4) understanding and interpreting data collected from patients with OA and depression, 5) taking part in a video used to train GPs and practice nurses in the new consultation model, 6) presenting research programme findings at conferences; and 7) a journal article about the development of the OA guidebook. 1 Conclusions: PPI provided a meaningful contribution to shaping, delivering and evaluating a complex research programme. The final programme report to the funder (NIHR) has a dedicated section on the contribution of PPI to the development, design, conduct and implementation of the research. References: Grime and Dudley. Health Expect. 2014 Apr;17(2):164-73. Acknowledgements: This presentation presents independent research funded by the National Institute for Health Research (NIHR) under its Programme Grants for Applied Research Programme (Grant Reference Number: RP-PG-0407-10386). Disclosure of Interest: None declared